2017
DOI: 10.1016/j.ydbio.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

CNS angiogenesis and barriergenesis occur simultaneously

Abstract: The blood-brain barrier (BBB) plays a vital role in the central nervous system (CNS). A comprehensive understanding of BBB development has been hampered by difficulties in observing the differentiation of brain endothelial cells (BECs) in real-time. Here, we generated two transgenic zebrafish line, Tg(glut1b:mCherry) and Tg(plvap:EGFP), to serve as in vivo reporters of BBB development. We showed that barriergenesis (i.e. the induction of BEC differentiation) occurs immediately as endothelial tips cells migrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
122
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(129 citation statements)
references
References 45 publications
(76 reference statements)
4
122
0
Order By: Relevance
“…The transport of small hydrophilic molecules or potentially harmful materials is tightly regulated by specific transport systems on luminal and abluminal membranes of the brain endothelium in an ATP‐mediated manner (Abbott, Ronnback, & Hansson, ). Importantly, these unique BBB functionalities are acquired via complex cellular interactions during developmental angiogenesis of the CNS (Engelhardt, ; Umans et al, ; Vallon, Chang, Zhang, & Kuo, ). Although some molecular mechanisms involved in BBB phenotypes have been discovered, the complex interplay between BBB cell types has yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transport of small hydrophilic molecules or potentially harmful materials is tightly regulated by specific transport systems on luminal and abluminal membranes of the brain endothelium in an ATP‐mediated manner (Abbott, Ronnback, & Hansson, ). Importantly, these unique BBB functionalities are acquired via complex cellular interactions during developmental angiogenesis of the CNS (Engelhardt, ; Umans et al, ; Vallon, Chang, Zhang, & Kuo, ). Although some molecular mechanisms involved in BBB phenotypes have been discovered, the complex interplay between BBB cell types has yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CNS angiogenesisspecific molecular systems, such as Glut-1, are regulated by Wnt-βcatenin signaling, which is related to barrier-specific properties (Daneman et al, 2009;Obermeier et al, 2013). Umans et al (2017) also reported that barrier genesis of BBB occurs simultaneously with CNS angiogenesis in vivo using the zebrafish mutant model. These examples clearly show the strong interconnection between the maturation of BBB functionality and CNS angiogenesis ( Figure 1b).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This specialized endothelial layer forms the blood-brain barrier (BBB) and restricts the passage of substances between the blood and the brain parenchyma via two primary mechanisms: 1) specialized tight junction complexes between apposed endothelial cells to prevent intercellular transit (Reese and Karnovsky, 1967; Brightman and Reese, 1969) and 2) suppressing vesicular trafficking or transcytosis to prevent transcellular transit (Ben-Zvi et al, 2014; Andreone et al, 2015; Andreone et al, 2017). BBB selectivity is further refined with expression of substrate-specific transporters that dynamically regulate the influx of necessary nutrients and efflux of metabolic waste products (Sanchez-Covarrubias et al, 2014; Umans et al, 2017). While the BBB is comprised of endothelial cells, the surrounding perivascular cells including pericytes and astroglial cells, play a critical role in forming and maintaining barrier properties (Janzer and Raff, 1987; Armulik et al, 2010; Bell et al, 2010; Daneman et al, 2010; Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As the simplest genetic model organism with an endothelial BBB (Jeong et al, 2008), zebrafish offer a powerful tool to study the cellular and molecular properties of the vertebrate BBB (Xie et al, 2010; Vanhollebeke et al, 2015; Umans et al, 2017; O’Brown et al, 2018; Quiñonez-Silvero et al, 2019). Zebrafish have served as a great model system to study vascular biology due to their large clutch size, rapid and external development, and transparency for in vivo whole organism live-imaging (Lawson and Weinstein, 2002; Jin et al, 2005; Santoro et al, 2007; Armer et al, 2009; Herbert et al, 2009; Phng et al, 2009; Geudens et al, 2010; Herbert et al, 2012; Wilkinson and van Eeden, 2014; Franco et al, 2015; Vanhollebeke et al, 2015; Matsuoka et al, 2016; Ulrich et al, 2016; Galanternik et al, 2017; Stratman et al, 2017; Geudens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%